The dynamics of band (peak) shape development in capillary zone electrophoresis in light of the linear theory of electromigration - Dvořák, Martin; Dubský, Pavel; Dovhunová, Magda; Gaš, Bohuslav (Electrophoresis, 2019)
The continuity equations that describe the movement of ions in liquid solutions under the influence of an external stationary electric field, as it is utilized in electrophoresis, were introduced a long time ago starting with Kohlrausch in 1897. From that time on, there have been many attempts to solve the equations and to discuss the results. In electrophoresis, special attention has always been devoted to the peak shapes obtained by the detector since the shapes have a tight connection with the phenomena taking place during electromigration and influence the efficiency and selectivity of the separation. Among these phenomena, the most important is electromigration dispersion. In this commented review paper, we compare various models of electromigration, try to find points that connect them, and discuss the range of their validity in light of the linear and nonlinear theory of electromigration.
Keywords: ionty; Capillary zone electrophoresis; Linear theory of electromigration; chemické modely; Electromigration dispersion; Ions; Models, Chemical; statistické modely; Models, Statistical; Electrophoresis, Capillary; elektroforéza kapilární